Competitive Intelligence in Biotech Start-Ups: Strategies for Capturing and Leveraging Market Insights (Journal of Informatics Education and Research, 2024)
The biotechnology sector is characterized by rapid technological advancements, intense competition, and dynamic market conditions. For start-ups operating in this space, the ability to capture and leverage competitive intelligence (CI) is crucial for gaining a strategic edge. This research paper explores the role of competitive intelligence in enhancing the competitiveness and sustainability of biotech start-ups. It delves into strategies for collecting, analyzing, and applying market insights to inform decision-making, optimize resource allocation, and drive innovation. The paper highlights best practices in CI, common challenges faced by biotech start-ups, and solutions to overcome these barriers. Through an in-depth examination of CI frameworks and real-world case studies, the research underscores how well-executed competitive intelligence can position biotech start-ups for long-term success. The findings contribute to a clearer understanding of how start-ups can build robust CI processes and use them to adapt to market changes, identify growth opportunities, and mitigate risks.